On the discernment of perception - Nussbaum, Martha; Santos-Ihlau, Rosa Helena (Estudios de Filosofía, 1995)
The aim of the present essay is to stake out the grounds of Aristotle' s theory of rationality and based on the aforesaid prernises to criticise contemporary theories of choice. In this fashion, an opposition is established at the heart of Aristotle's claims concerning practical rationality, wherein practical wisdom is set apart from scientific understandirrg and recent theories which lay out a supposedly "scientific" conception of practical rationality, or which envisage the possibility of deriving scientific reasoning from practical reasoning. In Martha Nussbaum's critical reflection nonetheless, contemporary views are not stretched past breaking point, since resort thereto is fashioned from the stance of an exhaustive interpretation of Aristotle's theory of practical rationality which effectively constitutes the main thrust of this article. To round off, a literary case is put forward with a view to illustrating and penetrating further Aristotelian criteria on personal choice.